SIDE EFFECTS FACTORS AFFECT THE COMPLIANCE OF ANTIRETROVIRAL TREATMENT IN PLWHS: STUDY OF UNDATA DISTRICT GENERAL HOSPITAL, PALU - Defi - -; Suharyo Hadisaputro; Muchlis Achsan U.Sofro (Dian Nuswantoro Semarang, 2020)
Background : Antiretroviral treatment currently starts in all people with HIV / AIDS, namely children, adolescents, and adults regardless of clinical stage or CD4 cell count. This is an effort to reduce the time needed to start ARV therapy after being diagnosed with HIV but taking into account the readiness of people with HIV / AIDS. Objective: To prove the age, sex, occupation, and history of side effects to adherence to ARV treatment in PLWHA.Method: Quantitative approach using the type of Case-Control research. The sample in this study was 35 cases and 35 controls. The sampling technique in this study was done by consecutive sampling, collecting data obtained from interviews using research instruments namely questionnaires and patient medical record reports. Statistical analysis using SPSS 25 with a chi-square test. Results: Proven to influence the adherence of ARV treatment in PLWHA were a history of side effects (p = 0.002). those not proven to affect the adherence of ARV treatment in PLWHA were Age (p = 0.189) Gender (p = 1.00) Occupation (p = 0.297). Conclusion: A history of side effects has been shown to influence ARV treatment.Keywords: HIV/AIDS, ARVs, Compliance